(untitled) (Comprehensive Journal of Science, 2026)
Background and Objectives: Pisiforms syndrome is a common chronic injury in athletes resulting from pisiforms muscle spasm and sciatic nerve compression (Spine-health, 2023) This study aimed to evaluate the effectiveness of an integrated 8- week functional rehabilitation program with repeated follow-up measurements in improving muscle strength and dynamic balance in male athletes with this syndrome. Methods: A one-group repeated measures experimental design (pretest - first follow-up - second follow-up - posttest) was used The main sample included 20 male athletes diagnosed with pisiforms syndrome after excluding 5 individuals from the pilot study Ages ranged from 20 -35 years Participants underwent an 8-week rehabilitation program (3 sessions/week) combining PNF, PIR, PFS techniques, strengthening and balance exercises (Maher, Hassan, & Ajman, 2025; Bashir et al., 2025) Muscle strength was measured using a hand-held dynamometer (Kiser, Colby, & Boasted, 2022) dynamic balance using the Y-Balance Test (Plucky et al., 2021) and pain using the Visual Analog Scale (VAS). Results: Significant improvements were found in all variables (p < 0.01) Mean hip flexor strength improved from 18.3 ± 3.2 kg to 28.7 ± 2.8 kg (56.8% improvement) hip extensor strength from 22.5 ± 3.5 kg to 34.2 ± 3.1 kg (52.0% improvement) and hip abductor strength from 16.8 ± 2.9 kg to 26.5 ± 2.7 kg (57.7% improvement) The Y-Balance composite score improved from 78.4% ± 5.3% to 89.1% ± 4.2% (45.3% improvement) and mean pain score decreased from 6.8 ± 1.2 to 2.1 ± 0.8 (69.1% reduction) Follow-up measurements showed a gradual improvement curve across program phases. Conclusion: The proposed functional rehabilitation program effectively improves muscle strength dynamic balance and reduces pain in male athletes with pisiforms syndrome. This integrated program with follow-up measurements is recommended for rehabilitation protocols.